Die rhombische und rhomboedrische Netze im dreidimensionalen euklidischen Raum - Padervinskas, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Падервинскас. Ромбические и ромбоэдрические сети в трехмерном евклидовом пространстве V. Padervinskas. Rombiniai ir romboedriniai tinklai trimatėje euklidinėje erdvėje